Metoda končnih elementov: Zbirka rešenih primerov - Skrinar, Matjaž (University of Maribor Press, 2020)
Finite Element Method: Collection of Solved Examples. The finite element method (FEM) is certainly the most widely used modern method for solving mechanical problems of structural analysis in civil engineering. Although typical problem areas of its implementation include not only static structural analysis but also dynamics and stability problems is this material intentionally limited to static analysis of plane line elements where ordinary differential equations in one variable are solved. The reason for this deliberate limitation is the fact that this work is intended to the students who meet with this method for the first time. Therefore, this work does not cover just typical civil engineering problems solved by the finite element but also covers some examples where the solutions are obtained through the variational methods which are the predecessors from which the finite element method was derived from.